Layanan Responsif: Kolaborasi Guru Bk Dan Orang Tua Dalam Meningkatkan Prestasi Belajar Peserta Didik - Yurianto, Ardini Farzana; Susanti, Dyah Amelia; Kasih, Zelma Setya; Habsy, Bakhrudin All (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
This research aims to explore the role of collaboration between Guidance and Counseling (BK) teachers and parents in improving student learning achievement through the implementation of responsive services. The research problem faced is how collaboration between guidance and counseling teachers and parents can influence student learning achievement in the school environment. The research population was high school-level students, with samples selected randomly from various schools. The research method used is a literature study, where various literature sources related to collaboration between guidance and counseling teachers and parents, as well as the implementation of responsive services, are analyzed comprehensively. The results of the analysis conclude that effective collaboration between guidance and counseling teachers and parents can significantly improve student learning achievement. Furthermore, the findings highlight the importance of parental involvement in education as well as the role of guidance and counseling teachers in providing responsive services that suit students' needs. The implication of this research is the importance of strengthening collaboration between guidance and counseling teachers and parents to support student learning and development. This research contributes to the understanding of how collaboration between guidance and counseling teachers and parents can be an effective strategy for improving student learning achievement.